Fostering an ethos of cultural humility development in nurturing inclusiveness and effective intercultural team working. (15th August 2021) - Markey, Kathleen; Prosen, Mirko; Martin, Emer; Repo Jamal, Hanna
Abstract: Aim: To discuss the importance of fostering an ethos of cultural humility development in cultivating inclusiveness and effective intercultural team working. Background: Widening cultural and ethnic diversity of the health care workforce enriches the working environment and encourages a broader perspective on health care services and delivery. However, the intricacies of learning to work effectively within intercultural health care teams and adapting to new ways of working are often under estimated and thus overlooked. Evaluation: In adopting a framework for cultural humility development (Hughees et al., 2020, 10.1016/j.profnurs.2019.06.005), this paper proposes some practical suggestions for nurturing intrapersonal, interpersonal and system level cultural humility simultaneously. Key Issues: Fostering an ethos of cultural humility development within the workplace can support inclusiveness and better intercultural team working relationships. Nurses need support in developing awareness of their own cultural beliefs, whilst examining perceptions of cultural difference. Conclusion: Examining cultural factors that influence intercultural working relationships will help in identifying structures, supports and approaches required for integration and inclusiveness. Implications for Nursing Management: Nurturing ways of supporting interpersonal, intrapersonal and systems levels cultural humility development inspires the self‐awareness, openness and respect for cultural difference required. Developing culturally responsive leadership styles and prioritizing their own cultural humility development is critical.